Initial Transcriptomic Response and Adaption of Listeria monocytogenes to Desiccation on Food Grade Stainless Steel - Kragh, Martin Laage; Truelstrup Hansen, Lisbeth (Frontiers in Microbiology, 2020)
The foodborne pathogen Listeria monocytogenes survives exposure to a variety of stresses including desiccation in the food industry. Strand-specific RNA sequencing was applied to analyze changes in the transcriptomes of two strains of L. monocytogenes (Lm 568 and Lm 08-5578) during desiccation (15°C, 43% relative humidity) on food grade stainless steel surfaces over 48 h to simulate a weekend with no food production. Both strains showed similar survival during desiccation with a 1.8-2 Log CFU/cm2 reduction after 48 h. Analysis of differentially expressed (DE) genes (>2-fold, adjusted p-value < 0.05) revealed that the initial response to desiccation was established after 6 h and remained constant with few new genes being DE after 12, 24 and 48 h. A core of 81 up- and 73 down-regulated DE genes were identified as a shared, strain independent response to desiccation. Among common upregulated genes were energy and oxidative stress related genes e.g., qoxABCD (cytochrome aa3) pdhABC (pyruvate dehydrogenase complex) and mntABCH (manganese transporter). Common downregulated genes related to anaerobic growth, proteolysis and the two component systems lmo1172/lmo1173 and cheA/cheY, which are involved in cold growth and flagellin production, respectively. Both strains upregulated additional genes involved in combatting oxidative stress and reactive oxygen species (ROS), including sod (superoxide dismutase), kat (catalase), tpx (thiol peroxidase) and several thioredoxins including trxAB, lmo2390 and lmo2830. Osmotic stress related genes were also upregulated in both strains, including gbuABC (glycine betaine transporter) and several chaperones clpC, cspA and groE. Significant strain differences were also detected with the food outbreak strain Lm 08-5578 differentially expressing 1.9× more genes (726) compared to Lm 568 (410). Unique to Lm 08-5578 was a significant upregulation of the expression of the alternative transcription factor σB and its regulon. A number of long antisense transcripts (lasRNA) were upregulated during desiccation including anti0605, anti0936, anti1846 and anti0777, with the latter controlling flagellum biosynthesis and possibly the downregulation of motility genes observed in both strains. This exploration of the transcriptomes of desiccated L. monocytogenes provides further understanding of how this bacterium encounters and survives the stress faced when exposed to dry conditions in the food industry.